Pelatihan Pemanfaatan Media Sosial Untuk Promosi Wisata Air Terjun Batu Dinding Kabupaten Kampar Provinsi Riau - Rusmadi Awza; Muhammad Firdaus; Ismandianto Ismandianto; Noor Efni Salam; Muchid Muchid (Lembaga penelitian dan pengabdian kepada masyrakat, 2023)
The development of well-planned tourist objects not only brings economic benefits that increase the level, quality and standard of living of the local community, but also improves and maintains a good environment. The purpose of this activity is to: Provide understanding and knowledge to the people of Kampar Kiri Hulu District, Kampar Regency about the use of social media for the Batudinding Waterfall tourist attraction. The teaching methods used to support the success of the program include lectures and questions and answers. This method was chosen to explain material that is theoretical in nature and related to tourism awareness and the Batudinding waterfall demonstration. This method is used to explain the process of working in stages so that participants can follow the process of tourism potential carefully. The impacts of this useful activity are: 1) the community is able to develop and promote tourism at Batudinding Waterfalls through social media, 2) increase the knowledge of the Pokdarwis of Tanjung Belit Village about the community's economic potential in the field of tourism, 4) increase the creativity of the community in processing natural resources around the village.